2022
DOI: 10.3389/fonc.2022.857714
|View full text |Cite
|
Sign up to set email alerts
|

miR-139-5p Was Identified as Biomarker of Different Molecular Subtypes of Breast Carcinoma

Abstract: Located on chromosome 11q13.4, miR-139-5p has been confirmed by several studies as a possible attractive biomarker for cancer, including breast cancer, but its mechanism of correlation in different molecular subtypes of breast cancer has not been reported. In this study, comprehensive bioinformatics analysis was used to evaluate the expression of miR-139-5p in different molecular subtypes of breast cancer (luminal A, luminal B, HER2-enriched, and basal-like). The target genes of miR-139-5p were predicted by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
3
1
Order By: Relevance
“…Contrary to our results, miR-139-5p had previously found downregulated in BC [ 22 , 44 ]. We have found no other article in agreement with our results and have no explanation for this disagreement.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our results, miR-139-5p had previously found downregulated in BC [ 22 , 44 ]. We have found no other article in agreement with our results and have no explanation for this disagreement.…”
Section: Discussioncontrasting
confidence: 99%
“…The guide strand derived from precursor-miR-139 is miR-139-5p, on which many studies have been conducted [23,24]. In cancer research, the downregulation of miR-139-5p has been reported in most cancer types (e.g., breast, gastric, colorectal, bladder, and head and neck cancers, among others) [25][26][27][28][29]. In contrast, a high expression of miR-139-5p has been reported in cancer tissues compared with normal tissues in gastrointestinal stromal tumors [23,30].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been demonstrated that human bone marrow mesenchymal stem cells are able to inhibit BC cells’ growth through the release of exosome cargo with miR-139-5p [ 98 ].…”
Section: The C-mirnas Shared Among the Selected Studiesmentioning
confidence: 99%